Endoplasmic reticulum stress in the salivary glands of patients with primary and associated Sjögren’s disease, and non-Sjögren’s sicca syndrome: a comparative analysis and the influence of chloroquine - Graziela Vieira Cavalcanti; Fabiola Reis de Oliveira; Rafael Ferraz Bannitz; Natalia Aparecida de Paula; Ana Carolina Fragoso Motta; Eduardo Melani Rocha; John Chiorini; Hilton Marcos Alves Ricz; Denny Marcos Garcia; Maria Cristina Foss-Freitas; Luiz Carlos Conti de Freitas (Advances in Rheumatology)
Abstract Background Endoplasmic reticulum stress (ERS) and the unfolded protein response (UPR) are adaptive mechanisms for conditions of high protein demand, marked by an accumulation of misfolded proteins in the endoplasmic reticulum (ER). Rheumatic autoimmune diseases (RAD) are known to be associated with chronic inflammation and an ERS state. However, the activation of UPR signaling pathways is not completely understood in Sjögren’s disease (SD). This study evaluated the expression of ERS-related genes in glandular tissue of patients with primary SD (pSD), associated SD (aSD) with other autoimmune diseases, and non-Sjögren sicca syndrome (NSS). Methods In a cross-sectional study, minor salivary gland biopsies were obtained from 44 patients with suspected SD and 13 healthy controls (HC). Patients were classified as pSD, aSD, or NSS based on clinical, serological, and histological assessment. Histopathological analysis and mRNA expression analysis of genes associated with ERS and UPR (PERK, XBP1, ATF-6, ATF-4, CANX, CALR, CHOP, and BIP) were performed on the samples. Differences between groups (pSD, aSD, NSS, and HC) were assessed. The influence of chloroquine (CQ) on the ER was also investigated. Results Twenty-eight SD patients showed increased expression of PERK (p = 0.0117) and XBP1 (p = 0.0346), and reduced expression of ATF-6 (p = 0.0003) and CHOP (p = 0.0003), compared to the HC group. Increased expression of BIP (p < 0.0001), PERK (p = 0.0003), CALR (p < 0.0001), and CANX (p = 0.0111) was also observed in the SD group compared to the NSS group (n = 16). Patients receiving CQ (n = 16) showed a significant increase in ATF-6 (p = 0.0317) compared to patients not taking the medication (n = 29). Conclusions Altogether, the results suggest a greater activation of the ERS and UPR genes in patients with SD, especially in the pSD group. Antimalarial drugs, like CQ, used to treat RAD, may affect the ER function in exocrine glands.